A Descriptive Study to Assess the Measures Adopted by Mothers to Reduce Behavioral Problems in Children Aged 6–12 Years in Selected Urban Areas of District Shimla, Himachal Pradesh - Kiran Dautoo, Shashi; Rekha, B. (International Journal of Nursing Research, 2023)
Aim: This study aims to assess the measures adopted by mothers to reduce behavioral problems among children in selected urban areas. Methodology: Quantitative research approach and descriptive research design were applied. The research was conducted in the urban areas of Sanjauli, Shimla District, Himachal Pradesh. Sample size was 200 mothers and purposive sampling technique was used. Results: The results of the present study reveal that majority of mothers adopted the measures to reduce behavioral problems in children for temper tantrum was 11.5% avoided situation likely to stimulate the child, for nail biting 11.5% kept hands busy and cut the nails of child, for thumb-sucking 10.5% those praised for behavior change and kept hands busy, for enuresis (bed wetting) 12.0% made the child void before bedtime and reward for dry nights, for stammering 3.0% avoided stress and practiced speech training, for school phobia 8.5% of mothers adopted measures like praise for regular attendance at school, for anorexia nervosa 2.0% of mothers supervised meals and snacks and monitored the weight, for bulimia nervosa 1.5% avoided over feeding the child and monitor the weight, for breathholding spells 1.0% used distractive methods, stay calm, provide safe environment, and provide proper ventilation, for aggressiveness 27.0% tried anger management, for pica 13.0% gave positive reinforcement and kept the child away from mud, clay, chalks, etc., for somnambulism (waking in sleep) 6.5% kept close supervision, avoided bunk bed, and stayed most of the time with the child, for somniloquy (talking in sleep) 9.5% made sleep schedule and avoided emotional stress, for bedtime fears and nightmares 9.0% avoided scary television shows, and for lying 26.5% of mothers shared their values, whereas for shyness 19.0% of mothers stay with child in social situations Conclusions: The study results show that measures adopted followed by mothers to deal with behavioral problems of their children that 197 (98.5%) mothers, the measures adopted level followed by mothers were “poor” and 3 (1.5%) mothers were followed average measures.